Pengaruh Model Pembelajaran Langsung Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas VIII di SMP Negeri 1 Jerowaru - Yuliana Susanti (Pendidikan Al-Gafari, 2024)
The problem of education cannot be separated from human life at all. Education for human life is an absolute life that must be fulfilled throughout life. Without education, a group of people will find it difficult to live and develop in line with their ideals to progress. This study aims to determine the effect of direct learning models on student learning outcomes in social studies subjects for class VIII at SMP Negeri 1 Jerowaru. This study uses an experimental method. Data collection techniques use documentation and tests. Sampling was carried out using the cluster random sampling technique, namely taking two classes randomly and placing class VIIID as the experimental class and class VIIIE as the control class, the experimental group was given the application of direct learning while the control class was not given the application of the direct learning model. Student learning outcome data was obtained using a test. The data collected was then analyzed using statistical analysis techniques, the formula used was the t-test formula. Based on the results of data analysis, the t count was obtained as much as 1.692 and the t table value at a significant level of 5% with db = 27 + 27 – 2 = 52 was 1.671, this shows that the t count is greater than the t table (1.692 > 1.671). Thus, it can be concluded that the direct learning model has an effect on student learning outcomes in the subject of social studies in class VIII at SMP Negeri 1 Jerowaru.